La lucha de clases en la antigua Grecia (G. E. M. de Ste. Croix, The Class Struggle in the Ancient Greek World, from the Archaic Age to Arab Conquests, Londres, Duckworth, 1981, XI +732 pp.). - Domingo Plácido (Gerión, 1983)
Sin resumen